2018
DOI: 10.3892/br.2018.1136
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetics of oral and oropharyngeal cancers (Review)

Abstract: Oral and oropharyngeal cancers represent the two most common malignancies of the head and neck region. The major risk factors for these cancers include alcohol consumption, tobacco use (via smoking or chewing) and high-risk human papillomavirus infection. The transition from normal epithelium to premalignant tissue and finally carcinoma is in part caused by a summation of genetic and epigenetic modifications. Epigenetic refers to modifications in the way the genome is expressed in cells. The most common exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 110 publications
0
18
0
1
Order By: Relevance
“…In this context, the role of non-coding RNAs, of which miRNAs are the most studied, has been recently acquiring remarkable importance in the development of several pathologies, including cancer [26,27,28]. In particular, several studies demonstrated that miRNAs, a class of small non-coding RNAs with a length of 20–22 nucleotides, are involved in cancer, including that of oral cavity cancer, inducing epigenetic modifications altering key cellular processes, such as cell differentiation, growth, apoptosis and drug resistance [29,30]. Notably, miRNAs are able to regulate gene expression by controlling mRNA translation, either by translational repression of the targeted mRNA or by enhancing its degradation through an RNA interference mechanism [31].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the role of non-coding RNAs, of which miRNAs are the most studied, has been recently acquiring remarkable importance in the development of several pathologies, including cancer [26,27,28]. In particular, several studies demonstrated that miRNAs, a class of small non-coding RNAs with a length of 20–22 nucleotides, are involved in cancer, including that of oral cavity cancer, inducing epigenetic modifications altering key cellular processes, such as cell differentiation, growth, apoptosis and drug resistance [29,30]. Notably, miRNAs are able to regulate gene expression by controlling mRNA translation, either by translational repression of the targeted mRNA or by enhancing its degradation through an RNA interference mechanism [31].…”
Section: Introductionmentioning
confidence: 99%
“…As the incidence of HPV-associated oropharyngeal carcinoma continues to rise, expanding our knowledge of epigenetic drivers that regulate HPV pathogenesis in the oropharyngeal epithelium is an important area of future research. Even though epigenetic modifications in HPV-associated oropharyngeal cancers, including DNA methylation and histone modifications, have been reported [152], the role of the DNA damage response in the epigenetic regulation of the viral life cycle in oropharyngeal epithelium remains uncharacterized. This is especially important, as recent studies indicate that the viral genome is episomal in a large number of head and neck cancers [153].…”
Section: Discussionmentioning
confidence: 99%
“…Oral/oropharyngeal carcinogenesis mostly depends on environmental factors, such as tobacco and alcohol abuse, particularly in the oral cavity, and persistent infection from HR-HPV in a rising percentage of oropharyngeal cancers. Thus far, only a few reliable prognostic markers have been reported, alone or in combination, for OSCC and OPSCC [35,36,37,38,39].…”
Section: Discussionmentioning
confidence: 99%